2015
DOI: 10.1002/cite.201500002
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and Hydrothermal Gasification of Microalgae Scenedesmus Obliquus – First Experimental Results

Abstract: Microalgae (Scenedesmus obliquus) produced in flat panel photobioreactors were converted via supercritical water gasification. The long term aim is to gain higher process efficiency through recycling of byproducts of supercritical water gasification and waste water during the cultivation of microalgae. The first step of the project, the general feasibility of conversion of microalgae Scenedesmus obliquus via supercritical water gasification to a hydrogen-rich combustible gas is presented. The product gas had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Unlike anaerobic digestion, SCWG is not currently commercially available and some technological challenges have to be overcome. The conditions of supercritical water (SCW; T > 374 °C, p > 22.1 MPa) offer several advantages: (i) a low salt solubility allowing the separation of the minerals prior to gasification; , (ii) tar and coke formation is reduced because of the high solubility of organic substances in SCW. , Many research papers have reported continuous SCWG of several microalgae species at high temperatures (600–700 °C). Elsayed et al performed SCWG (600–650 °C, 28 MPa) of Scenedesmus obliquus (2.5–5% dry matter, DM) over a continuous period up to 50 h. The carbon gasification efficiency was above 90% and the gas consisted of H 2 (46 vol %), CH 4 (19 vol %), CO 2 (29 vol %), and C 2 H 6 (4.5 vol %). Patzelt et al have gasified (650 °C, 28 MPa) Acutodesmus obliquus (2.5–5% DM) over a period of 50 h with a flow rate of 4.8 g min –1 and observed a gasification efficiency up to 98%.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike anaerobic digestion, SCWG is not currently commercially available and some technological challenges have to be overcome. The conditions of supercritical water (SCW; T > 374 °C, p > 22.1 MPa) offer several advantages: (i) a low salt solubility allowing the separation of the minerals prior to gasification; , (ii) tar and coke formation is reduced because of the high solubility of organic substances in SCW. , Many research papers have reported continuous SCWG of several microalgae species at high temperatures (600–700 °C). Elsayed et al performed SCWG (600–650 °C, 28 MPa) of Scenedesmus obliquus (2.5–5% dry matter, DM) over a continuous period up to 50 h. The carbon gasification efficiency was above 90% and the gas consisted of H 2 (46 vol %), CH 4 (19 vol %), CO 2 (29 vol %), and C 2 H 6 (4.5 vol %). Patzelt et al have gasified (650 °C, 28 MPa) Acutodesmus obliquus (2.5–5% DM) over a period of 50 h with a flow rate of 4.8 g min –1 and observed a gasification efficiency up to 98%.…”
Section: Introductionmentioning
confidence: 99%